Inhibition of Nef- and phorbol ester-induced CD4 degradation by macrolide antibiotics. - Luo, T (1996)
Human immunodeficiency virus type 1 (HIV-1) is the causative agent of AIDS. The simian immunodeficiency virus (SIV) causes a similar syndrome in macaques. The product of the nef gene of SIV has been shown to be important for virus replication and disease progression in vivo. In vitro, both SIV and HIV Nef downregulate surface expression of CD4 and accelerate total CD4 turnover. The mechanism by which Nef downregulates CD4 has not been established. A current model suggests that Nef enhances cell surface CD4 endocytosis and degradation in lysosomes. However, this was recently challenged when CD4 was found to accumulate in early endosomes of cells expressing Nef. Because inhibition of Nef function might halt virus replication and disease progression, we tested two macrolide antibiotics for their ability to inhibit Nef function. Concanamycin B (ConB) and bafilomycin A1 (BFLA1) are specific inhibitors of acidification of cell endosomes and lysosomes and, unlike other inhibitors, do not affect transport. Although ConB (25 nM) and BFLA1 (100 nM) blocked phorbol myristate acetate- and Nef-induced CD4 degradation in human monocyte U937 cells, CD4 surface expression was not recovered. Instead, CD4 accumulated in lysosomes. To determine if Nef is directly responsible for CD4 degradation or if they bind to each other in a manner similar to Vpu, transcripts of human CD4 and HIV-1 nef were cotranslated in vitro. Our results indicate that under our experimental conditions, Nef does not affect CD4 stability and does not associate with CD4 in this in vitro system. Our data suggest that (i) CD4 downregulation by Nef results in degradation of CD4 in lysosomes, (ii) inhibition of CD4 degradation by macrolide antibiotics does not restore surface expression, and (iii) the inhibition of CD4 expression by Nef appears to be indirect and is likely to involve cellular factors.